Bones. The complete seventh season [videorecording (DVD)] - Hanson, Hart; Boreanaz, David, 1971-; Deschanel, Emily, 1976-; Conlin, Michaela; Taylor, Tamara, 1970-; Thyne, T. J., 1975-; Daley, John Francis (Bones (Television program), 2012)
While she tackles some of her most gruesome homicide cases yet, Dr. Temperance Brennan also faces the delicate demands of motherhood and a deepening relationship with FBI Special Agent Seeley Booth. The thrills escalate this season when a pastor's wife goes missing and shipping clerks go postal, but the biggest shocker of all comes when clues left by a deranged cyber genius tag Brennan as a murder suspect.